INDUSTRI TELEVISI DAN ANCAMAN DEMOKRASI - Setio Budi HH (IKOM UMY, 2015)
RCTI is the first commerciol television in lndonesia and it wos signal as the end of the state television (TVRI). The roise of the commercial television after RCTI it shown of new development of television business industry in lndonesia. The presence of commerciol television is also one of the indicator in threatening the democrocy. One of the indication of that threat is about the ownership of the television industry. Until now, 11 stations owned by 11 owner is consolidated in to three mojor players : liNC Group, Para Group and Bokrie Group, This situation should be monitored due to the impact to the public at large, speciolly in democrocy issues.